An evaporite sequence from ancient brine recorded in Bennu samples - T. J. McCoy; S. S. Russell; T. J. Zega; K. L. Thomas-Keprta; S. A. Singerling; F. E. Brenker; N. E. Timms; W. D. A. Rickard; J. J. Barnes; G. Libourel; S. Ray; C. M. Corrigan; et al. (Nature, 2025)
Abstract Evaporation or freezing of water-rich fluids with dilute concentrations of dissolved salts can produce brines, as observed in closed basins on Earth 1 and detected by remote sensing on icy bodies in the outer Solar System 2,3 . The mineralogical evolution of these brines is well understood in regard to terrestrial environments 4 , but poorly constrained for extraterrestrial systems owing to a lack of direct sampling. Here we report the occurrence of salt minerals in samples of the asteroid (101955) Bennu returned by the OSIRIS-REx mission 5 . These include sodium-bearing phosphates and sodium-rich carbonates, sulfates, chlorides and fluorides formed during evaporation of a late-stage brine that existed early in the history of Bennu’s parent body. Discovery of diverse salts would not be possible without mission sample return and careful curation and storage, because these decompose with prolonged exposure to Earth’s atmosphere. Similar brines probably still occur in the interior of icy bodies Ceres and Enceladus, as indicated by spectra or measurement of sodium carbonate on the surface or in plumes 2,3 .